Estrategias metodológicas para el fortalecimiento de la ortografía en el área de lengua y literatura con los estudiantes de quinto año de educación básica de la escuela “6 de junio” de la parroquia Pimocha, cantón Babahoyo, provincia los Ríos en el año 2017 - Alvarado Cavero, Erika Daniela (2017)
The teaching-learning process is linked to the strategies, methods and instruments used by teachers to bring students to meaningful learning. Nevertheless theories like the one of Maria Montessori says that the child must be allowed to find the solution to his problems, being himself the one who constructs new knowledge based on his concrete experiences, which indicates that each student has his way of understanding and to grasp knowledge . It is here that the teacher must intervene because it is the fundamental pillar in the educational process and who must implement strategies in an efficient way always trying to strengthen the weaknesses that are presented in the teaching learning process and for students to acquire a knowledge of it shape. In this way the educator will be able to consolidate the contents in the area of Language and Literature. Emphasizing the problem of inappropriate use of orthographic rules presented by students, the imperative need to find and implement appropriate pedagogical mechanisms to achieve the optimization of this language skill, such as the design of a guide methodological strategies to strengthen knowledge of spelling in the teaching process, of the students and thus will be able to contribute to the development of education. Spelling is a vital aspect of language learning, particularly in the process of developing writing skills and habits.